INVESTIGATING HIGHER EDUCATION COURSE LEADERSHIP PRACTICE – AN ARGUMENT FOR USING GROUNDED THEORY - Nieky van Veggel; Hilary Engward; Philip Howlett (Novìtnâ Osvìta, 2023)
The study of course leadership in higher education focusses on an understudied area of research, with a limited number of publications discussing the role of the course leader in higher education, and a distinct lack of research on how course leaders in higher education undertake their professional practice. This lack of a pre-existing theory points the researcher towards grounded theory to investigate and generate a new theory on course leaders’ experiences. Since leadership, and therefore course leadership, is an inherent complex social process, selection of grounded theory as a research methodology to explain how course leaders in higher education practice seems a logical choice. Grounded theory has been successfully used to investigate phenomena in education and in leadership practice in other disciplines. We therefore argue that grounded theory is an appropriate selection for research in education and higher education settings for areas of research where no theory currently exists. Moreover, grounded theories focussing on professional practice have been published in various contexts demonstrating that it is an appropriate method for investigating course leaders’ professional practice. Finally, this paper outlines some perceived weaknesses of using a grounded theory approach for researching course leadership, and offers means to navigate these.